Association of Performance on the Financial Capacity Instrument–Short Form With Brain Amyloid Load and Cortical Thickness in Older Adults. Issue 2 (April 2022) - Vassilaki, Maria; Aakre, Jeremiah A.; Kremers, Walter K.; Mielke, Michelle M.; Geda, Yonas E.; Machulda, Mary M.; Knopman, David S.; Vemuri, Prashanthi; Lowe, Val J.; Jack, Clifford R.; Roberson, Erik D.; Gerstenecker, Adam; et al.
Abstract : Background and Objectives: To investigate the association of the Financial Capacity Instrument–Short Form (FCI-SF) performance and timing total scores with brain β-amyloid and cortical thickness in cognitively unimpaired (CU) (at baseline) older adults. Methods: A total of 309 participants (aged 70 years or older) of the Mayo Clinic Study of Aging underwent 11 C-Pittsburgh compound B PET amyloid imaging and MRI, and completed the FCI-SF. Abnormal amyloid PET was defined as standardized uptake value ratio ≥1.48 in an Alzheimer disease (AD)-related region of interest and reduced AD signature cortical thickness as ≤2.68 mm (neurodegeneration). A cohort of 218 (of the 309) participants had follow-up visits (every 15 months) with FCI-SF data for longitudinal analysis (number of visits including baseline, median [range]: 2 [2–4]). In the analysis, we used linear regression and mixed-effects models adjusted for age, sex, education, apolipoprotein E ε4 allele status, global cognitive z score, and previous FCI-SF testing. Results: Participants' mean age (SD) was 80.2 (4.8) years (56.3% male individuals). In cross-sectional analysis, abnormal amyloid PET (vs normal) was associated with a lower FCI-SF total score and slower total composite time. In longitudinal analysis, FCI-SF total score declined faster (difference in annualized rate of change, beta coefficient [β] [95% confidence interval (CI)] = −1.123 [−2.086 to −0.161]) and FCI-SF total composite time increased faster (difference in annualized rate of change, β [95% CI] = 16.274 [5.951 to 26.597]) for participants with neurodegeneration at baseline (vs those without). Participants who exhibited both abnormal amyloid PET and neurodegeneration at baseline had a greater increase in total composite time when compared with the group without abnormal amyloid and without neurodegeneration (difference in annualized rate of change, β [95% CI] = 16.750 [3.193 to 30.307]). Discussion: Performance and processing speed on the FCI-SF were associated with imaging biomarkers of AD pathophysiology in CU (at baseline) older adults. Higher burdens of imaging biomarkers were associated with longitudinal worsening on FCI-SF performance. Additional research is needed to delineate further these associations and their predictive utility at the individual person level.